GADD45α is involved in the apoptosis of lymphocytes induced by riboflavin and ultraviolet light. Issue 3 (1st December 2016) - Yang, Peng; Wen, Huiqin; Zhong, Tao; Hu, Hailiang; Zhu, Bangqiang; Xia, Kang; Xu, Mo; Bian, Maohong
Abstract : BACKGROUND: Riboflavin plus ultraviolet (UV) pathogen reduction technology (RF‐PRT) is an effective method for inactivating the residual white blood cells (WBCs) in blood components. The RF‐PRT system for platelets is known to activate many signaling pathways, including p38 and NF‐κB. Nevertheless, proteomic studies in WBCs after riboflavin plus UV treatment requires further analysis. STUDY DESIGN AND METHODS: ABO/D‐matched lymphocytes were pooled, split, and treated with RF‐PRT or UV light or left untreated. After treatment, cell apoptosis was measured. In addition, cell proliferation and the cycle distribution were evaluated upon stimulation with phytohemagglutinin. The changes in the protein expression levels of growth arrest and DNA damage‐inducible (GADD)45α, p38, and c‐Jun N‐terminal kinase (JNK) were determined by Western blotting. The effect of GADD45α, p38, and JNK on apoptosis was assessed. RESULTS: RF‐PRT significantly inhibited proliferation and induced G1 arrest in lymphocytes. Furthermore, the percentage of apoptotic cells was increased in RF‐PRT–treated lymphocytes compared to UV‐treated cells or untreated cells, associated with the up regulation of GADD45α expression. Consistent with these observations, the inhibition of GADD45α expression partially counteracted the effects of riboflavin plus UV treatment. The p38 and JNK signaling pathways were activated by GADD45α in RF‐PRT–treated lymphocytes. CONCLUSIONS: These data revealed that RF‐PRT effectively inhibited proliferation and induced apoptosis of lymphocytes by promoting GADD45α expression, which subsequently activates p38 and JNK signaling pathways.